Hungarian Monitoring, 26 November 1989 . [Magyar rádiófigyelő], 1989. november 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's article in Pravda on perestroika - Czechoslovakia: talks start in Prague between authorities and the masses; Czechoslovak CP Central Committee session Domestic Affairs: - Night of the referendum - 24-member committee evaluates Hungary's ecological situation - Hungarian opposition parties write letter promising support to Czechoslovak opposition - Interview in Paris with Dr. Otto Habsburg Economy: - Hungarian Post Office becomes public limited company Külpolitika: - M. Gorbacsov cikke a Pravda hasábjain a peresztrojkáról - - Csehszlovákia:Prágában megkezdődött a párbeszéd a hatalom és a tömegek között ; CSKP KB ülés Belpolitika: - A népszavazás éjszakája - Magyarország ökológiai helyzetét értékelte egy 24 tagú bizottság - Magyar ellenzéki pártok levélben biztosították szolidaritásáról a csehszlovák ellenzéket - Párizsi interjú Dr. Habsburg Ottóval Gazdaság: - A Posta részvénytársasággá alakulása